The qualitative researcher, the suffering parent and the children’s services professional: an enquiry into the theory and practice of psychoanalytically-informed interviewing in social work research - Archard, Philip John (2019)
This thesis enquires into the application of concepts and practices associated with psychoanalysis (as a broad therapeutic tradition linked by a concern for what is unconscious) in qualitative social work research. It is specifically concerned with the theory and practice of psychoanalytically-informed research interviewing. The first half of thesis considers the application of free association and the use of therapeutic interpretation in interviews. It also provides a critical account of Hollway and Jefferson’s (2000, 2013) “free association narrative interview method” - a well-known approach to research interviewing and analysis (at least amongst scholars interested in the extrapolation of psychoanalytic principles to extra-clinical qualitative research) that is grounded in a framework combining aspects of psychoanalytic and discursive psychology. The second half of the thesis then relates findings from an empirical study informed by this method which sought to explore how children’s services professionals experience the suffering of parents in their work via 33 interviews with 15 participants. The reporting of this research allows for further consideration of how interview narratives can be understood from a psychoanalytically-informed perspective, and how participants experience being the subjects of this type of study. It also illustrates how insights from psychoanalytically based psycho-social theory can be used for enquiring into the ways in which parents figure in the minds of children’s services professionals and how their capacity to hold the suffering parent in mind relates to working conditions and practices, and individual and organisational psychodynamics. Overall, in addressing these different tasks, the thesis makes a contribution, firstly, in rectifying a lack of critical concern amongst social work researchers with the free association narrative interview method. Secondly, and more broadly, it develops and refines understanding about the relationship between psychoanalysis and qualitative research interviewing, the quasi-therapeutic qualities of research interview participation, and the nature of psycho-social understanding in social work research.